Enhanced photocatalytic degradation of methylene blue using zinc oxide nanoparticles grown on microscopic silicon dioxide / Nur Azmina Mohamed Safian - Nur Azmina , Mohamed Safian (2019)
Photocatalysis is the acceleration of chemical reactions on semiconductor catalysts surfaces with the assistance of light. Photocatalysis efficiency is dependent on catalysts total surface area, band gap and photon energy and intensity. The advent of nanosized photocatalyst such as ZnO and TiO2 nanoparticles (NPs) has generated interest in the benefit of size effect and significant increase of surface area of these materials which is crucial for process efficiency. To overcome the problem of NPs agglomeration, a study on the fabrication and application of pure, doped and Ag NPs decorated ZnO NPs on microscopic silicon dioxide namely sand microparticles have been conducted. Sand microparticles were found to be efficient support for ZnO NPs growth on nanosized pits and grooves provided excellent adhesion. The photocatalytic activity was found to be significantly enhanced where photodegradation efficiency of methylene blue (MB) using supported ZnO NPs reached 71.7 % compared to 48.2 % for unsupported ZnO NPs under UV light irradiation within 150 minutes. The photodegradation rate constant, k increased from 0.0043 min-1 to 0.0086 min-1 for unsupported and supported ZnO NPs, respectively. The modification on the band gap of supported ZnO NPs photocatalyst was done by doping with Al and Ag. Supported ZnO NPs doped with Al and Ag have been applied for photodegradation of MB and showed a better photocatalytic activity than supported pure ZnO NPs. The photodegradation efficiency and value of k increased to 83.1 % and 0.0106 min-1, respectively using supported Al-doped ZnO NPs at 0.034 Al/Zn ratio. The highest value of first and second photodegradation rate constant, k1 and k2 for supported Ag-doped ZnO NPs samples was obtained from 0.024 of Ag/Zn ratio which are 0.0129 min-1 and 0.0289 min-1, respectively. The increased photocatalytic activity mainly due to the changes in the optical properties of ZnO NPs where prevent the charge recombination adequately. In addition, the modification on the surface of photocatalyst was done to improve the photocatalytic activity by decorating supported ZnO NPs with Ag NPs. The supported Ag NPs-decorated ZnO NPs at 0.42 of Ag/Zn ratio show highest value of k1 and k2 around 0.0191 and 0.0409 min-1, respectively. The improvement of photocatalytic performance was mainly due to the Ag acting as electron sinks, thus increasing the electron-hole lifetime.